Effect of oxygen vacancies on the electrical properties of Bi(6)Ti(5)TeO(22) thin film - Choi, Chang-Hak; Choi, Joo-Young; Cho, Kyung-Hoon; Yoo, Myong-Jae; Nahm, Sahn; Kang, Chong-Yun; Yoon, Seok-Jin; Kim, Jong-Hee (ELECTROCHEMICAL SOC INC, 2008)
Bi(6)Ti(5)TeO(22) film grown under a low oxygen pressure (OP) of 0.21 Pa showed a low breakdown field of 0.25 MV/cm which increased with increasing the OP to 0.60 MV/cm for the film grown under the OP of 0.59 Pa. The breakdown field decreased when the OP exceeded 0.59 Pa, due to the formation of oxygen interstitial ions. A small amount of Mn doping also increased the breakdown field of the Bi(6)Ti(5)TeO(22) films grown under a low OP. These improvements were related to the decreased number of intrinsic oxygen vacancies identified by the variation of metallic telluride states in the photoemission spectra of the Te 3d level. (C) 2008 The Electrochemical Society.
Keywords: MIM CAPACITORS; CERAMICS; SUBSTRATE